Maya is solving the quadratic equation by completing the square.

4x2 + 16x + 3 = 0

What should Maya do first?

Isolate the variable x2.
Subtract 16x from both sides of the equation.
Isolate the constant.
Factor 4 out of the variable terms.

Respuesta :

Step-by-step explanation:

factor 4 out of the variable terms, as this helps.

but my approach is simply to define the target and then calculate "backwards".

we want to find

(ax + b)² = a²x² + 2abx + b²

and now we compare with the original equation :

a²x² = 4x²

a² = 4

a = 2

2abx = 16x

2×2×bx = 16x

4b = 16

b = 4

b² = 16, but we have only 3, so we need to subtract 16-3 = 13 from the completed square.

so, our equation is

(2x + 4)² - 13 = 0

(2x + 4)² = 13

2x + 4 = sqrt(13)

2x = sqrt(13) - 4

x = sqrt(13)/2 - 2

Answer:

Isolate the constant.

Step-by-step explanation:

Given quadratic equation:

[tex]4x^2+16x+3=0[/tex]

Completing the Square

Step 1

Isolate the constant by subtracting 3 from both sides:

[tex]\implies 4x^2+16x+3-3=0-3[/tex]

[tex]\implies 4x^2+16x=-3[/tex]

Step 2

Factor out the coefficient of x² from the left side:

[tex]\implies 4(x^2+4x)=-3[/tex]

Divide both sides by 4:

[tex]\implies x^2+4x=-\dfrac{3}{4}[/tex]

Step 3

Add the square of half the coefficient of x to both sides.  This forms a perfect square trinomial on the left side:

[tex]\implies x^2+4x+\left(\dfrac{4}{2}\right)^2=-\dfrac{3}{4}+\left(\dfrac{4}{2}\right)^2[/tex]

Simplify:

[tex]\implies x^2+4x+4=-\dfrac{3}{4}+4[/tex]

[tex]\implies x^2+4x+4=\dfrac{13}{4}[/tex]

Step 4

Factor the perfect square trinomial on the left side:

[tex]\implies (x+2)^2=\dfrac{13}{4}[/tex]

We have now completed the square.  

To solve, square root both sides:

[tex]\implies \sqrt{(x+2)^2}=\sqrt{\dfrac{13}{4}}[/tex]

[tex]\implies x+2=\pm\sqrt{\dfrac{13}{4}}[/tex]

[tex]\implies x+2=\pm\dfrac{\sqrt{13}}{\sqrt{4}}[/tex]

[tex]\implies x+2=\pm\dfrac{\sqrt{13}}{2}[/tex]

Subtract 2 from both sides:

[tex]\implies x+2-2=-2\pm\dfrac{\sqrt{13}}{2}[/tex]

[tex]\implies x=-2\pm\dfrac{\sqrt{13}}{2}[/tex]

Rewrite -2 as -4/2:

[tex]\implies x=-\dfrac{4}{2}\pm\dfrac{\sqrt{13}}{2}[/tex]

[tex]\textsf{Apply the fraction rule}\quad \dfrac{a}{c} \pm \dfrac{b}{c}=\dfrac{a \pm b}{c}:[/tex]

[tex]\implies x=\dfrac{-4 \pm\sqrt{13}}{2}[/tex]

Learn more about completing the square here:

https://brainly.com/question/27933930

https://brainly.com/question/27591531